E-077 Surveillance imaging of unruptured, untreated intracranial aneurysms: a review of the literature. (22nd July 2018) - Hall, N; Froehler, M
Abstract : Background: Intracranial aneurysms affect approximately 2% to 4% of the population, with aneurysmal rupture causing potentially devastating subarachnoid hemorrhage. Improved imaging technologies and more frequent intracranial screening has led to incidental findings of asymptomatic unruptured intracranial aneurysms (UIAs). While the role for microsurgical clipping and endovascular embolization has been well established for those carrying a high risk of rupture, many UIAs are managed conservatively. These untreated UIAs are routinely followed with intracranial vascular imaging to monitor signs of growth or change in morphology, which may suggest an impending rupture. Current evidence is clear that different aneurysms carry differing risks of growth/rupture. Because of the varying risks, a 'one-size-fits-all' serial imaging protocol may not be appropriate nor cost-effective. Methods: The PubMed database was used to search for full text publications discussing risk factors for aneurysm growth and rupture, and/or the frequency and duration of surveillance imaging for untreated UIAs that are managed conservatively. The following keywords were used in various combinations: 'intracranial aneurysm, ' 'unruptured, ' 'surveillance, ' 'follow-up, ' 'imaging, ' 'incidental, ' 'conservative, ' 'risk of growth, ' 'risk of rupture, ' 'time.' Results: Twenty-five articles were initially identified as discussing relevant aneurysm risk factors, timing of growth or rupture, and/or recommendations for conservative management of UIAs. Of these, 2 prospective studies and 3 meta-analyses/systematic reviews studied the timing of aneurysm growth or rupture, but did not provide clear recommendations for frequency nor duration of surveillance imaging of UIAs. Three clinical practice guidelines were identified, although no specific recommendations were provided. Finally, 3 retrospective studies provided either the frequency and duration of imaging protocol used in the study or clear recommendations for surveillance imaging (table 1). Inoue and colleagues (2012) recommended repeating imaging every six months, based on a higher rate of aneurysm growth detection with biannual compared with annual imaging. The study of the PHASES aneurysm risk score (2017) and a study by Serrone, et al . (2016) both used protocols with increasing time window between each vascular imaging study with aneurysm stability. Discussion: The role of conservative management of UIAs is well established, particularly in the setting of increasing frequency of incidental UIA findings. It is generally agreed upon that the UIAs left untreated be monitored for signs of growth or morphologic change over time, but the specific frequency and duration of imaging has not been clearly defined. Current evidence has established that different aneurysms carry different risks of growth and rupture, depending on both aneurysm- and patient-specific factors, highlighting the need for risk-based surveillance imaging recommendations. Future research considerations regarding serial imaging of untreated UIAs include identifying an evidence-supported imaging protocol accounting for aneurysm risk factors and evaluating for cost-effectiveness of such a protocol for the routine surveillance imaging of untreated UIAs. Disclosures: N. Hall: 1; C; NIH StrokeNet. M. Froehler: 1; C; Medtronic, Stryker, Microvention, EndoPhys, NIH. 2; C; Medtronic, Stryker, NeurVana, Balt, Control Medical, Genentech, Viz.ai.